2002
DOI: 10.1046/j.1365-2222.2002.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposome‐entrapped D. pteronyssinus vaccination in mild asthma patients: effect of 1‐year double‐blind, placebo‐controlled trial on inflammation, bronchial hyper‐responsiveness and immediate and late bronchial responses to the allergen

Abstract: Liposome-entrapped D. Pteronyssinus vaccination: (i) protects mild asthma patients from the worsening of asthma due to sustained mite exposure; and (ii) reduces the functional and inflammatory changes induced by allergen bronchial provocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…This confirms the results of other controlled trials investigating the effect of SIT administered by subcutaneous injection on methacholine responsiveness in subjects with respiratory allergy[7,30,31]. By contrast, other investigations identified a significant improvement in methacholine responsiveness after SIT with house dust mites[23,27] or pollen allergens[24,25]. Reasons to such discrepancies are not evident, but might be related to differences in patients' characteristics, to diversity in the disease activity in the subjects studied, to differences in the characteristics of the allergenic extract administered, or to important differences in the statistical analysis.…”
Section: Discussionsupporting
confidence: 87%
“…This confirms the results of other controlled trials investigating the effect of SIT administered by subcutaneous injection on methacholine responsiveness in subjects with respiratory allergy[7,30,31]. By contrast, other investigations identified a significant improvement in methacholine responsiveness after SIT with house dust mites[23,27] or pollen allergens[24,25]. Reasons to such discrepancies are not evident, but might be related to differences in patients' characteristics, to diversity in the disease activity in the subjects studied, to differences in the characteristics of the allergenic extract administered, or to important differences in the statistical analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Nine studies reported on FEV1. Reporting of data was varied . (Table ) Data pooled from two studies indicated no clear evidence of benefit associated with AIT with an SMD of 0.41 (95% CI −0.46, 1.27; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At T12, before the allergen challenge, serum ECP levels increased in the placebo group and blood eosinophils showed a trend toward lower numbers in the active group. The immediate response and the changes in Mch‐DRS values, sputum eosinophils, and serum ECP levels, following the allergen challenge, were attenuated in the active group …”
Section: Evaluation Of the Body Of Evidencementioning
confidence: 94%